Pemanfaatan abu serbuk kayu dan serbuk cangkang kerang sebagai material stabilisasi tanah lunak - Irvan Ustuchri; Anita Setyowati Srie Gunarti; Sri Nuryati; Elma Yulius; Eko Darma; Ninik Paryati; Fajar Prihesnanto (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2023)
Muara Gembong Sub-district, Bekasi Regency, West Java Province, has many damaged and bumpy roads. This area is coastal and some parts of the area are swampy soils that have low bearing strength, not meeting the required bearing strength (CBR) of at least 6%. This research aims to analyze the effect of the addition of sawdust ash and clam shell powder as soil stabilization material on bearing strength, in this case the California Bearing Ratio value. The method used in this research is a laboratory experiment of soft soil stabilization mixed with additive materials in the form of sawdust ash and clam shell powder at a proportion of 2% and 4% to the dry weight of the soil. Tests carried out include Atterberg limit test, compaction, and CBR in unsubmerged conditions. The analysis showed that the soil mixed with 4% clam shell powder without sawdust ash increased the CBR value by 84.32% against the original soil CBR. Soil mixed with clam shell powder and sawdust ash also experienced an increase in bearing strength but not as good as soil mixed with clam shell powder alone.